Comparison of Student Business Success at Universitas Pendidikan Indonesia and the National Movement of 1000 Digital Startups - Ridwan, Ilham Daffa; Fauziyah, Azizah; Rachmani, Nizza Nadya (J-MAS (Jurnal Manajemen dan Sains), 2025)
This study aims to compare the business success of Entrepreneurship Study Program students of Universitas Pendidikan Indonesia (UPI) with participants of the National Movement of 1000 Digital Startups (1000S) in West Java, based on five indicators: sales growth (X1), customer growth (X2), customer retention (X3), product/service validation (X4), and business efficiency (X5). This research uses a descriptive quantitative approach with comparative analysis between two groups. The samples used were 10 UPI students and 10 1000S participants. The results showed that of the five variables tested, the 1000S group had a significant advantage in the variables of sales growth (X1), customer growth (X2), and customer retention (X3) over the UPI group. The workshop-based entrepreneurship program was more effective in improving several aspects of business success.